Developmental Assessments in Preterm Children: A Meta-Analysis - Wong,HS; Santhakumaran,S; Cowan,FM; Modi,N (Pediatrics, 2016)
CONTEXT: Developmental outcomes of very preterm (gestational age ≤32 weeks) or very low birth weight (<1500 g) children are commonly reported before age 3 years although the predictive validity for later outcomes are uncertain.OBJECTIVE: To determine the validity of early developmental assessments in predicting school-age cognitive deficits.DATA SOURCES: PubMed.STUDY SELECTION: English-language studies reporting at least 2 serial developmental/cognitive assessments on the same population, 1 between ages 1 and 3 years and 1 at ≥5 years.DATA EXTRACTION: For each study, we calculated the sensitivity, specificity, and positive and negative predictive values of early assessment for cognitive deficit (defined as test scores 1 SD below the population mean). Pooled meta-analytic sensitivity and specificity were estimated by using a hierarchical summary receiver operator characteristic curve.RESULTS: We included 24 studies (n = 3133 children). Early assessments were conducted at 18 to 40 months and generally involved the Bayley Scales of Infant Development or the Griffiths Mental Development Scales; 11 different cognitive tests were used at school-age assessments at 5 to 18 years. Positive predictive values ranged from 20.0% to 88.9%, and negative predictive vales ranged from 47.8% to 95.5%. The pooled sensitivity (95% confidence interval) of early assessment for identifying school-age cognitive deficit was 55.0% (45.7%–63.9%) and specificity was 84.1% (77.5%–89.1%). Gestational age, birth weight, age at assessment, and time between assessments did not explain between-study heterogeneity.LIMITATIONS: The accuracy of aggregated data could not be verified. Many assessment tools have been superseded by newer editions.CONCLUSIONS: Early developmental assessment has poor sensitivity but good specificity and negative predictive value for school-age cognitive deficit.